A Relação de influência entre o processo decisório e a escolha racional na eficiência operacional de instituições públicas de ensino superior - RIBEIRO, Fernando Maia (Universidade Federal do Pará, 2025)
The objective of this research was to analyze the relationship of influence between the decision-making process, rational choice and operational efficiency. Rational actions tend to be influenced by the decision-making process, which, together, influence organizational efficiency. Decision-making based on rationality has been the subject of studies in several theoretical and empirical studies. In the field of rational choice, there is extensive literature involving private sector entities; however, few studies are found regarding public sector organizations. The efficient execution of operations in public administration has been increasingly demanded by society, especially after Constitutional Amendment No. 19/1998, which introduced the principle of efficiency in the Brazilian constitution, imposing that public administration be exercised with promptness, quality, perfection, effectiveness and functional performance. The reality exposed was motivating for carrying out this research, which demonstrated the importance of rational decision-making by public managers to improve organizational efficiency. Thus, exploratory research was conducted with a quantitative approach, using the field research technique, through the application of 167 questionnaires to decision-makers in Public Higher Education Institutions in the city of Belém, state of Pará. Our findings show, through the theoretical model adopted in the research, that the Decision-Making Process directly influences Rational Choice and Operational Efficiency. In turn, Rational Choice directly influences Operational Efficiency, that is, there is a strong interrelationship between the Decision-Making Process, Rational Choice and Operational Efficiency constructs. Exploratory factor analysis explains 59% of the variance of the proposed model. Another finding of this research is the confirmation that rational choice mediates the relationship between the Decision-Making Process and Operational Efficiency with a statistical significance level lower than 0.05%. With a relevant and original approach, the research contributes to scientific and academic knowledge by investigating the interaction of two constructs in a performance proxy based on rational choice theory. That said, it points to the behavior of managers adopting a growth and agile mindset, even in public organizations that adopt a more traditional type of management, since managers aim to improve decision-making in a rational way, even when they are in an environment of uncertainty and constant evolution. In the social sphere, this research contributes to better practices in the provision of services offered to society, in a timely and high-quality manner, guiding, in some way, institutional governance. Finally, it also contributes, in managerial terms, that operational efficiency, when stimulated by rational choice based on decision-making, makes the Decision-Making Process more feasible